Genetic characterization of GSD I in Serbian population revealed unexpectedly high incidence of GSD Ib and 3 novel SLC37A4 variants. Issue 2 (11th December 2017) - Skakic, A.; Djordjevic, M.; Sarajlija, A.; Klaassen, K.; Tosic, N.; Kecman, B.; Ugrin, M.; Spasovski, V.; Pavlovic, S.; Stojiljkovic, M.
Abstract : Glycogen storage disease (GSD) type I is inborn metabolic disease characterized by accumulation of glycogen in multiple organs. We analyzed 38 patients with clinical suspicion of GSD I using Sanger and next‐generation sequencing (NGS). We identified 28 GSD Ib and 5 GSD Ia patients. In 5 patients, GSD III, VI, IX, cholesteryl‐ester storage disease and Shwachman‐Diamond syndrome diagnoses were set using NGS. Incidences for GSD Ia and GSD Ib were estimated at 1:172 746 and 1:60 461 live‐births, respectively. Two variants were identified in G6PC gene: c.247C>T (p.Arg83Cys) and c.518T>C (p.Leu173Pro). In SLC37A4 gene, 6 variants were detected. Three previously reported variants c.81T>A (p.Asn27Lys), c.162C>A (p.Ser54Arg) and c.1042_1043delCT (p.Leu348Valfs*53) accounted for 87% of all analyzed alleles. Computational, transcription studies and/or clinical presentation in patients confirmed pathogenic effect of 3 novel variants: c.248G>A (p.Gly83Glu), c.404G>A (p.Gly135Asp) and c.785G>A (p.Ser263Glyfs*33 or p.Gly262Asp). In the cohort, hepatomegaly, hypoglycemia and failure to thrive were the most frequent presenting signs of GSD Ia, while hepatomegaly and recurrent bacterial infections were clinical hallmarks of GSD Ib. All GSD Ib patients developed neutropenia while 20.6% developed inflammatory bowel disease. Our study revealed the highest worldwide incidence of GSD Ib. Furthermore, description of 3 novel variants will facilitate medical genetic practice. Abstract :